Analysis of Halal Certification for Micro and Small Business Actors from the Perspective of Maslahah Principles and Legal Certainty - Suhartini, Endeh; Hertiani, Euis; Djuniarsono, R.; Rumatiga, Hidayat; Sabila PM, Nurfajrina (al-'adalah, 2024)
Based on the latest data, the number of Muslim population in Indonesia is currently recorded at 245,973,915 people. They all need the availability of food and beverages that meet the provisions of sharia, namely halālan thayyibā food and beverages. For this reason, the Government, through Law Number 33 of 2014 concerning Halal Product Guarantee, requires every producer to produce food and beverages that are proven by having a halal certificate. One way to obtain the certificate is through the Halal Self Declare Program. This program is free and is intended only for Micro and Small Business Actors (MSEs). This study aims to discuss the halal certification program for micro and small entrepreneurs as well as the benefits of the program from the perspective of maslahah theory and legal certainty. The results of the study concluded that the Halal certification program can provide benefits to many parties, ranging from entrepreneurs, consumers, and also the Government. For business actors, the benefits obtained are greater than for business actors who do not have the certificate, especially in terms of increasing sales turnover. This is because consumers tend to choose products that are guaranteed halal rather than other products that are not or are not clear about their halalness. With the increase in turnover, the entrepreneur's income will automatically increase and will ultimately have a positive effect on the income of his employees